PENGARUH SIKAP, MOTIVASI DAN LINGKUNGAN KELUARGA TERHADAPMINAT BERWIRUSAHA PADA MAHASISWA ADMINISTRASI BISNIS KAMPUS PANGKALAN ASEM INSTITUT STIAMI ANGKATAN 2017 - 2020 - Nabila Sabrina; Abbas Mansyur; Zulkfili Zulkifli (JAMBIS : Jurnal Administrasi Bisnis, 2022)
The Impact of Attitude, Motivation and Family Environment on Interest in Entrepreneurship of Business Administration Students at the Pangkalan Asem Campus STIAMI Institute Batches of 2017 - 2020 The research aims to examine the impact of attitudes, motivations and family environment on entrepreneurial interest of Business Administration Students at the Pangkalan Asem campus of the STIAMI Institute batches of 2017 - 2020. The type of this research was associative causal research using a quantitative approach. Data collection was carried out using a questionnaire method distributed to respondents and processed using SPSS v26. The data used in this research are Primary data and Secondary data. The population in this research was Business Administration Students at the Pangkalan Asem Institute of STIAMI batches 2017 – 2020. The sample is taken with random sampling method. The sample used was 265 respondents determined by the slovin formula. The data analysis technique used is multiple linear regression. The results of this research show that (1) Attitude has a positive and significant effect on interest in Entrepreneurship 26,5% (2) Motivation has a positive and significant effect on interest in Entrepreneursip 51% (3) Family Environment has a positive and significant on interest in Entrepreneurship 10% (4) Attitude, Motivation and Family Environment simultaneously have a positive and significant effects on interest in Entrepreneurship 61% and 39% has been influenced by other factors which were not examined by the researcher.